PEMIKIRAN HOWARD GARDNER DALAM PENDIDIKAN ANAK USIA DINI - Muhibuddin Fadhli (Universitas Muhammadiyah Ponorogo, 2016)
Promises independence Indonesia has spoken by the agents of history, one promise is the co-educating the nation, of course, those promises have not been fully met, that generation has passed, but not with the spoken promise, that promise will remain imprinted in the minds of the generations thereafter , we have to participate repay the appointment, although mouth did not give yet a calling of souls who move the hearts and minds to intervene to guide the realization of this promise. By nature children are born with millions of uniqueness, even children are not always visible twins are similar in all respects, be aware that the duty to educate children inherent in every human being, to educate is to lead children and all human beings are born to be a leader. Educating is not the work, especially of that educating should be higher than just earn money, educate should be fair, be understandable, and brought the child to the noble human decency. This article will discuss educating children in terms of various aspects of the philosophical and theoretical thinking by Howard Gardner